Hubungan Prokrastinasi Akademik dengan Indeks Prestasi Kumulatif (IPK) Pada Mahasiswa Angkatan 2023 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi - Saranga, Rafael; Pangemanan, Damajanty H. C.; Tompodung, Linda M. (Medical Scope Journal, 2025)
Abstract: Academic procrastination is the failure to do tasks within the planned time span until the last moment. Academic procrastination has an impact on students in obtaining maximum learning outcomes because it can affect the cumulative grade point average (GPA) that will be obtained. The study aims to determine the relationship between academic procrastination and GPA of medical education students class of 2023 Sam Ratulangi University using questionnaires as primary data instruments with the Cross-sectional study method. The results showed that out of a total of 233 respondents who filled out the academic procrastination questionnaire, very high scores were obtained 18 (7.73%), high 119 (51.07%), moderate 79 (33.91%), low 13 (5.58%), and very low 4 (1.72%). GPA with honors 199 (85.41%), very satisfactory 31 (13.30%), and satisfactory 3 (1.39%). The Spearman rank correlation test obtained a p value> 0.05 and r = .088. The conclusion of this study is that the level of academic procrastination is classified as high category but there is no significant relationship between academic procrastination and cumulative grade point average. Keywords: Academic Procrastination; Cumulative Grade Point Average